2020
DOI: 10.5755/j01.sace.27.2.26079
|View full text |Cite
|
Sign up to set email alerts
|

Survey Based Evaluation of Indoor Environment in an Administrative Military Facility

Abstract: Military facilities feature distinctive requirements with regards to building technical and structural design, material use and indoor environmental conditions (IEC), as these buildings serve specific purpose and the personnel occupying the premises may wear uniform or protective clothing (administrative staff, special forces, training personnel etc.), that can greatly affect their satisfaction level with thermal comfort and productivity. In order to acquire data on the actual indoor environment conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, there are situations, such as business meetings or working in a dangerous environment, where protective clothing must be worn. In these situations, occupants cannot change their clothing level [79]. Moreover, the average occupants' clothing level changes throughout the year [80].…”
Section: Human Clothing Level Detection Systemsmentioning
confidence: 99%
“…However, there are situations, such as business meetings or working in a dangerous environment, where protective clothing must be worn. In these situations, occupants cannot change their clothing level [79]. Moreover, the average occupants' clothing level changes throughout the year [80].…”
Section: Human Clothing Level Detection Systemsmentioning
confidence: 99%
“…Construction work such as electrical installation, plumbing, and ventilation hatches -can be a detractor to the effectiveness of bullet-proof walls. Borodinecs et al have studied bullet safety and microclimate in unclassified buildings [2][3][4][5][6][7], also how ventilation ducts inside the panel affect wall ballistics. [8] Is a bullet-proof wall construction material available on the market that would be convenient and easy to install in an existing or new building, easy to transport, and highly fire-resistant?…”
Section: Introductionmentioning
confidence: 99%
“…is much higher in comparison to regular buildings, as the building envelope has a crucial role in maintaining heat balance and preserving heat loss from the building, accounting for up to 60% of building thermal performance [5], while in temporary shelters and tents the envelope oftentimes consist of light material with little to no insulation and protection from outdoor conditions. For instance, a recent study suggested that energy consumption in military facilities significantly exceeds that of residential buildings, mainly due to the poor thermal properties of military building stock [6].…”
Section: Introductionmentioning
confidence: 99%